Women & Self-harm : Understanding, Coping and Healing from Self-Mutilation. - Smith, Gerrilyn (Taylor & Francis, 2002)
Hundreds of thousands of women self-mutilate, yet very little is known about the reasons for this widespread phenomenon or the experience of self-harming itself. Now, this powerful and accessible book gathers together the personal testimonies of a broad range of women who self-mutilate, explores the causes and effects of self-harming behavior and offers strategies for understanding, overcoming and healing from self-mutilation.